Menumbuhkan Karakter Esensial Anak Usia Dini Melalui Kisah Si Belang (Sopak), Si Botak, dan Si Buta - Maisari, Sri; Rahimah, Rahimah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
Characters into the inherent value of a person's life. Essential character is the basic character tobe instilled in early childhood. In Islam include siddid character, trust, sermons, and fathonahwhich are properties of the Prophet Muhammad. Essential character will foster the growth ofother characters such as responsibility, caring, honest, hard working, diligent, intelligent, and soforth. This paper aims, 1) determine the essential character contained in the story of the stripes,bald, and blind, and 2) to foster the implementation of the essential character of early childhoodthrough the story of the stripes, bald, blind. Essential character is crucial grown from an earlyage, so that one day these characters attached to adult. The essential character of the story ofthe striped grown, bald, and the blind is in the form siddiq believe in Allah and grateful;mandate form of responsibility, persistent / hard work in raising livestock; Tabligh befriendly,caring and helpful; and fathonah be fathonah: smart in taking care of the cattle to berich